2011
DOI: 10.1007/s00405-011-1839-9
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of sinonasal lymphoma: a challenge for rhinologists

Abstract: The presenting symptoms of sinonasal lymphoma are usually similar to those of benign inflammatory diseases. Adequate amount of biopsy tissue is required for a definitive diagnosis because tumor coexisting with necrosis or inflammation is not uncommon. Therefore, the diagnosis of sinonasal lymphoma is a challenge for rhinologists. Thirty-two patients diagnosed as having sinonasal lymphoma from 1990 to 2010 in our hospital were included in this study. The presenting symptoms of these patients included nasal obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 25 publications
5
70
2
Order By: Relevance
“…(9) In a similar fashion, a definitive diagnosis of NK/T-cell lymphoma was only made in our patient after deep-seated histological specimens were obtained during FESS. This clearly shows that simple punch biopsies may not harvest adequate amounts of tissue in these patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…(9) In a similar fashion, a definitive diagnosis of NK/T-cell lymphoma was only made in our patient after deep-seated histological specimens were obtained during FESS. This clearly shows that simple punch biopsies may not harvest adequate amounts of tissue in these patients.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, surgical procedures such as FESS, turbinectomy or the Caldwell-Luc procedure have been reported to be more useful for harvesting adequate biopsy specimens for the pathological examination of sinonasal lymphoma. (9) In patients with persistent symptoms of sinusitis despite 'adequate' treatment, a high index of suspicion should be exercised for more sinister conditions such as nasal lymphoma. Apart from chronic sinusitis symptoms refractory to conventional treatment, our patient also had the red-flag 'B' symptoms of fever and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that T-cell and natural killer/ T-cell lymphomas mainly occur in the nasal cavity, whereas B-cell lymphomas commonly occur in the sinus without nasal disease (10,11). Clinically aggressive lymphomas, including Burkitt's lymphoma and diffuse large B-cell lymphoma of the sphenoid sinus, exhibit atypical characteristics, including destruction of adjacent bone such as the skull base and infiltration of the dura mater with intracranial invasion (12).…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in the diagnostic process leads to a presentation of an advanced stage of the lymphoma, which then predicts poor prognosis for the patient. As the nature of the disease is one of progressive tissue necrosis, multiple large biopsy specimens are required before sufficient tissue with scattered malignant cells is discovered [45][46][47][48][49][50]. Careful immunohistochemical assessment is thus vital in order to differentiate these lymphomas from other malignancies as well as benign inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients wait an average of 8.9 months to seek medical help after becoming aware of their symptoms. This late presentation in the office contributes to the advanced stage of lymphoma and thus associated poor prognosis [49].…”
Section: Discussionmentioning
confidence: 99%